Pengaruh Alih Fungsi Lahan Pertanian Menjadi Pemukiman Terhadap Aktivitas Masyarakat Di Desa Cikunir Kecamatan Singaparna - Shofa Zanjabila; Yuli Sri Hermawati; Ripa Siti Maptuah; Tiara Najmfathiana P; Fahrezi M Fadhil; Yani Sri Astuti (STIKes Ibnu Sina Ajibarang, 2024)
Land is a strategic resource that has economic value. Currently, the amount of agricultural land area continues to decrease each year. This reduction in the amount of agricultural land is the result of an increase in the number and activities of the population as well as development activities. The research method used in this research is qualitative. This research seeks to examine the conversion of agricultural land and its impact on the condition of community activities in Cikunir Village. Based on the research results, it is known that land conversion in Cikunir Village is a type of massive conversion. which has both negative and positive impacts. Almost the entire Cikunir Village area is now residential, even though previously it was an agricultural area. Residential land area in Cikunir Village 93,275 Ha (2024).